The role of ipsilateral premotor cortex in hand movement after stroke. - Johansen-Berg, H; Rushworth, M; Bogdanovic, MD; Kischka, U; Wimalaratna, S; Matthews, P (2002)
Movement of an affected hand after stroke is associated with increased activation of ipsilateral motor cortical areas, suggesting that these motor areas in the undamaged hemisphere may adaptively compensate for damaged or disconnected regions. However, this adaptive compensation has not yet been demonstrated directly. Here we used transcranial magnetic stimulation (TMS) to interfere transiently with processing in the ipsilateral primary motor or dorsal premotor cortex (PMd) during finger movements. TMS had a greater effect on patients than controls in a manner that depended on the site, hemisphere, and time of stimulation. In patients with right hemiparesis (but not in healthy controls), TMS applied to PMd early (100 ms) after the cue to move slowed simple reaction-time finger movements by 12% compared with controls. The relative slowing of movements with ipsilateral PMd stimulation in patients correlated with the degree of motor impairment, suggesting that functional recruitment of ipsilateral motor areas was greatest in the more impaired patients. We also used functional magnetic resonance imaging to monitor brain activity in these subjects as they performed the same movements. Slowing of reaction time after premotor cortex TMS in the patients correlated inversely with the relative hemispheric lateralization of functional magnetic resonance imaging activation in PMd. This inverse correlation suggests that the increased activation in ipsilateral cortical motor areas during movements of a paretic hand, shown in this and previous functional imaging studies, represents a functionally relevant, adaptive response to the associated brain injury.